The date and route of the Exodus - de Wit, C.; Tyndale Biblical Archaeology Lectures 1950.; Tyndale Fellowship for Biblical Research (London, UK Tyndale, 1960)
Includes bibliographical references.
Keywords: Bible. O.T. Exodus -- history of contemporary events